Heterovalent Trinuclear Co(III)-Co(II)-Co(III) Complexes with N-(2-Carboxyethyl)salicylaldimines - (:unkn) unknown (PLEIADES PUBLISHING INC, 2012)
The heterovalent trinuclear cobalt complexes [(Co2L4i)-L-III center dot Co-II(H2O)(4)] center dot nXmY (L-i are deprotonated Schiff bases derived from substituted salicylaldehydes and beta-alanine; i = 1-3) were obtained and characterized. An X-ray diffraction study of the trinuclear cobalt complex with N-(2-carboxyethyl)salicylaldimine showed that the central Co(II) ion and the terminal Co(III) ions are linked by bridging carboxylate groups. Either terminal Co(III) atom is coordinated to two ligand molecules. They form an octahedral environment consisting of two azomethine N atoms, two phenolate O atoms, and two O atoms of two carboxylate groups. The central Co(II) atom is coordinated to four water molecules and to two O atoms of two bridging carboxylate ligands involved in the coordination sphere of the terminal Co(III) atoms.
Keywords: COBALT COMPLEXES; CRYSTAL; VALENCE